High Interest in Long-acting Injectable Pre-exposure Prophylaxis (LAI-PrEP) for HIV Prevention Among Men Who Have Sex With Men (MSM): Result From A Nationwide Survey in Malaysia. - Paudel, Kiran; Gupta, Sana; Gautam, Kamal; Wickersham, Jeffrey A; Khati, Antoine; Azwa, Iskandar; Ha, Toan; Shrestha, Roman (Journal of Community Health, 2023)
The recent approval of long-acting injectable cabotegravir (CAB-LA) as PrEP for HIV prevention could be an attractive alternative for MSM, particularly among those who face barriers to adherence using the oral pill. This study reports on the awareness of long-acting injectable PrEP (LAI-PrEP) and factors associated with interest in LAI-PrEP use among a nationwide sample of MSM in Malaysia. An online cross-sectional survey was conducted between August and September 2021 to explore perspectives on PrEP modalities among Malaysian MSM (N = 870). Convenience sampling was used to recruit participants using ads on two platforms hornet and facebook. While only 9.1% of the study participants were aware of LAI-PrEP, the majority had heard of oral PrEP (80.9%). After giving a description of it, a large majority (86.6%) expressed interest in using it if made accessible. Those who had a prior history of HIV testing (aOR = 1.9; 95% CI = 1.2–3.2) were more likely to use LAI-PrEP. Interestingly, despite the concerns related to potential high cost (aOR = 3.4; 95% CI = 2.1–5.5) and long-term side effects (aOR = 1.9; 95% CI = 1.2–3.1), the majority of the participants were interested in using LAI-PrEP. Those who were afraid of (or disliked) syringes were less interested in using it (aOR = 0.2; 95% CI; 0.1–0.4). In the recent context that LAI-PrEP was shown to be safe and effective at preventing HIV, our results indicate its potential relevance as an additional PrEP option that could accelerate the uptake and scale-up of PrEP. However, it is crucial to conduct future research urgently to improve the understanding of strategies that could enhance the accessibility, acceptability, and affordability of LAI-PrEP for MSM in low- and middle-income countries, including Malaysia.